Post-corona unipolar chargers with tuneable aerosol size-charge relations: Parameters affecting ion dispersion and particle trajectories for charger designs. Issue 1 (2nd January 2021) - Jidenko, N.; Bouarouri, A.; Gensdarmes, F.; Maro, D.; Boulaud, D.; Borra, J.-P.
Abstract: This article focuses on the mean charge per particle of monodisperse submicron aerosols charged by the diffusion of unipolar ions in post-corona discharge. It aims to confirm and discuss the limits of considering a single value of Ni ·t to describe aerosol charging and then to present methods to control the size-charge relation. Three aerosol chargers with different mixings of ion and aerosol flows are investigated. Despite comparable ion sources with discharge currents of a few tens of µA, the size-charge relations differ from one charger to another due to different ion-aerosol mixing conditions and subsequent differences in ion density along the particles' trajectories. Discrepancies are even more noticeable as the particle size increases. Discharge current, velocities of ion and aerosol flows and the electric field control post-discharge ion density at each point of the charging zone. The control of particle trajectory in expanding unipolar ion clouds leads to tuneable size-charge relations. Aerosol inertia and charging dynamics both depend on particle size, affect the Ni ·t experienced by the particle and thus the final charge of the particle. Operating conditions to reach a constant mean charge for particles larger than 200 nm are reported. Conclusions provide a basis to design aerosol chargers devoted to electric mobility selection for aerosol deposition, separation or electrical measurements, especially to overcome the limits of mobility-to-size data inversion due to the multiple charge ambiguity inherent to diffusion chargers. Copyright © 2020 American Association for Aerosol Research